2018
DOI: 10.11591/ijeei.v6i4.518
|View full text |Cite
|
Sign up to set email alerts
|

Malayalam Handwritten Character Recognition Using AlexNet Based Architecture

Abstract: This research article proposes a new handwritten Malayalam character recognition model based on AlexNet based architecture. The Malayalam language consists of a variety of characters having similar features, thus, differentiating characters is a challenging task. A lot of handcrafted feature extraction methods have been used for the classification of Malayalam characters. Convolutional Neural Networks (CNN) is one of the popular methods used in image and language recognition. AlexNet based CNN is proposed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies were succussed in utilizing the previously learned parameters of AlexNet for extracting features in numerous HCR tasks [29,30]. It is observed that every time the training set increases, the AlexNet recognition rate also increases.…”
Section: Alexnet Fine-tuningmentioning
confidence: 99%
“…Several studies were succussed in utilizing the previously learned parameters of AlexNet for extracting features in numerous HCR tasks [29,30]. It is observed that every time the training set increases, the AlexNet recognition rate also increases.…”
Section: Alexnet Fine-tuningmentioning
confidence: 99%
“…A character-level text ConvNets is presented in [8] for English and Chinese corpus by transfer learning to endeavor and reuse the important portrayals that are found out in the ConvNets from an enormous scope dataset. AlexNet the most robust CNN which is pre-trained with the ImageNet dataset has been exploited for character recognition of many scripts like Devanagari [9], Malayalam [10], Korean [11], and Tamil [12]. Manually written Devanagari character acknowledgment has been introduced in [13] using layer-wise preparation of Deep CNN and accomplished great results using six different adaptive gradient methods.…”
Section: Introductionmentioning
confidence: 99%